2020
DOI: 10.5539/mas.v15n1p122
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Students and Faculty Members at Israa University towards Distance Learning in Light of the Corona Pandemic

Abstract: This study aimed to identify students' attitudes and faculty members at Israa University towards distance learning in light of the Corona pandemic. A questionnaire was developed that included two pictures (student photo/faculty member photo). Each image in the questionnaire consisted of (30) items distributed into three areas: Learning and teaching, assessment and testing, and learning and communication management, where acceptable coefficients of validity and reliability were achieved for the two ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, the easy-to-use features and exciting content uploaded by lectures may ignite students' interest to learn more from LMS and affect their learning results. Alshorman (2018) points out that LMS provides features that raise students' motivation to learn, such as audio, video, image, animation, games, and images. In particular, Zainuddin et al (2019) found that video lectures posted by lecturers evoke students' interest in online learning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the easy-to-use features and exciting content uploaded by lectures may ignite students' interest to learn more from LMS and affect their learning results. Alshorman (2018) points out that LMS provides features that raise students' motivation to learn, such as audio, video, image, animation, games, and images. In particular, Zainuddin et al (2019) found that video lectures posted by lecturers evoke students' interest in online learning.…”
Section: Discussionmentioning
confidence: 99%